The effect of eligibility for antiretroviral therapy on body mass index and blood pressure in KwaZulu-Natal, South Africa - Kuber, Aditi; Reuter, Anna; Geldsetzer, Pascal; Chimbindi, Natsayi; Moshabela, Mosa; Tanser, Frank; Bärnighausen, Till; Vollmer, Sebastian (Scientific reports, 2021)
We use a regression discontinuity design to estimate the causal effect of antiretroviral therapy (ART) eligibility according to national treatment guidelines of South Africa on two risk factors for cardiovascular disease, body mass index (BMI) and blood pressure. We combine survey data collected in 2010 in KwaZulu-Natal, South Africa, with clinical data on ART. We find that early ART eligibility significantly reduces systolic and diastolic blood pressure. We do not find any significant effects on BMI. The effect on blood pressure can be detected up to three years after becoming eligible for ART.
Gesehen am 06.10.2021